Pemanfaatan Metode Geolistrik Untuk Identifikasi Potensi Air Tanah Di Desa Madanddreng Pulu Kecamatan Patimpeng Kabupaten Bone - LM Yazid Amsah; And Ilham Samanlangi; Moh Khaidir Noor; Enni Tri Mahyuni; A Alfaiza Ma’rief; Surianti; Anna Irada La Ode Malim (Empowerment: Jurnal Pengabdian Masyarakat, 2023)
Water is one of the main basic needs for humans. This community service aims to provide information to the village government and the community regarding the availability of groundwater potential zones and provide recommendations for groundwater drilling depths. This activity is motivated by the fact that most of the people in Bone Regency, South Sulawesi Province, especially in Maddanreng Pulu Village, still rely on shallow groundwater (dug wells) to meet their clean water needs. The method used is the geoelectric method where data is taken directly in the field, the data from the measurements in the field are then analyzed to determine the groundwater potential zone which is the target for drilling in Maddanreng Pulu Village, Patimpeng District, Bone Regency. The geoelectrical measurement results obtained a resistivity value of 15.8 ohm.m as a layer that has the potential as an aquifer layer, the thickness of this layer reaches 161 meters starting from a depth of 13.3 to 174 meters.